Kajian Yuridis Terhadap Narapidana Yang Melakukan Pelanggaran Pidana Dalam Rumah Tahanan - Sofyan, Selviana; Natsir, Muhammad; Suardi, Suardi; Bimantoro, Tegar; Saharuddin, Saharuddin (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2025)
This research aims to determine the causes of violations committed by prisoners in detention centers and what the legal consequences are for prisoners who commit violations in detention centers. This research uses a normative-empirical research type. The results of this research show that the cause of criminal violations in detention is mostly due to overcapacity in the Pinrang class IIB state detention center and also because of feelings of resentment that have not been resolved previously outside detention and when they are reunited, these feelings of resentment reappear which cause emotions towards These prisoners also lack awareness for these prisoners, and as for the legal consequences for prisoners who commit criminal offenses in class IIB Pinrang state detention centers, these prisoners receive different sanctions according to the criminal offenses they have committed, which are categorized into three levels, namely moderate. For light, light, and heavy sentences, the prisoner is given a warning not to commit the same offense and the prisoner makes an oral or written statement not to repeat the act, then the medium sentence is given a sanction where the prisoner is put in a red cell or cell. exile for 6 (six) days and deprived of his rights for a while, such as not having visits from his family finally, this punishment is serious, this punishment is included in serious offenses where the prisoner will be put in solitary confinement for 6 (six) times 2 (two), and have their rights removed, such as not having visits from their family and their remission period could be revoked.